SDN OVERLAY NETWORKS DESIGN AND INVESTIGATION OF MAJOR FEATURES - Одарченко, Р. С.; Даков, С. Ю.; Поліщук, В. В.; Тирсенко, А. М. (Science-based technologies, 2016)
In this work the possibility of two methods of software driven network, such as Overlay and OpenFlow, and comparison of these methods with traditional IP network that the wireless Internet space of Ukraine, is dominant. A comparative analysis of variants of modern computer networks, including technology OpenFlow, Overlay and traditional IP. Development of virtual models, SDN and traditional methods in software Mininet and MiniEdit. The virtual model shows the effectiveness of transition from NAT to Overlay and OpenFlow, where Overlay can be deployed on any IP network, which will help save money. Using standard commands, found the delay of packets and using the software Mathcad calculations made addictions average delay on the number of packets in the flow and the number of switches in the network. Numbered and presented in graphical form statistical data confirming efficacy and promising networks SDN, and its greater efficiency from the traditional. Results of work can be used as a guide, personally it is important for Internet providers, what are at present already preparing for the transition to a more modern and technological 4G. Without a modern management system, it will be impossible.